Rooftop solar with net metering: An integrated investment appraisal - Majid Hashemi; Glenn P. Jenkins; Frank Milne (Queen's University, Department of Economics, 2022)
This paper develops a framework for a financial, economic, and stakeholder analysis of a residential rooftop solar net-metering program. The empirical focus of the paper is the net-metering program in Ontario, Canada, but the methodology is applicable to evaluating other public programs. The results highlight that without the Federal Government's subsidy for the initial investment cost, net-metered solar systems are not financially viable for representative households. Moreover, the stakeholder analysis reveals that for each additional net-metered system installed in Ontario, non-net-metered households experience financial losses of eight times the benefits to the net-metered households. The net losses to the Federal Government of Canada and the Canadian economy are six and twelve times the benefit to the net-metered households, respectively. The only stakeholder who benefits marginally is the Government of Ontario. In terms of environmental benefits, our estimate of the cost of greenhouse gas abatement by residential net-metered solar is 413 CAD per ton of CO 2e , which is significantly higher than the current (65 CAD in 2023) and future (170 CAD by 2030) social cost of carbon set by the Government of Canada.
Keywords: D61; L94; Q42; Q48; 330; rooftop solar; net metering; greenhouse gas emissions; renewable energy; the social cost of carbon; Canada